ANALISIS IMPLEMENTASI TATA RUANG KOTA BATU DALAM KONSEP KAWASAN AGROPOLITAN - AULIYA, AULIYA (2008)
The Development of Batu City as Agropoly region meant to serve, push, pull, and support Batu City development activity. In geographical view, Batu City located on position 7055 30 to 7057 30 South Pole and 115017 0 to 118019 0 East Longitude. Batu City topography was mountain range with 600-3000 m upper the sea line. Batu City is one of East Java Province region with 199.087 km2 wide or 19.908,72 hectare with 169.816 people at 2004, density level 847 people per km, including 3 sub-districts. They were Batu sub-district, Junrejo sub-district, and Bumiaji sub-district. According to geographical, topographic, temperature, and city arrangement distribution condition at Batu City, there were some region including : protected forest region, disaster risk region, and work region. To optimize the resource arrangement and keep the maintenance of agropoly region, every usage of existing resource should pay attention to the arrangement. Batu City Geographical location supporting for farm commodity, whether food plant or horticulture (vegetables, fruits, and decoration plant). Beside, there was also developed sub-sector like cow and chicken farms. This research was study at Bapeda BPS Batu City, titled Batu City Arrangement Plan in Agropoly Region Concept This research aimed to find out the Batu City Arrangement Plan in agropoly development concept. Knowing potential tool owed by Batu City as Agropoly Region. Analysis tool used in this research was qualitative descriptive, useful to describe the research object in real way. The agropoly region development plan in Batu City Region got several entry, as : (1) most of Batu Citizen support the agropoly region at Batu City region because : (a) create better wealth of Batu citizens (b) fix the farm product marketing system (c) could do farm development continuously (d) fix the farmer society economic through the increasing of continuous farm commodity (2) Agropoly region create better prospect. (3) solving problems faced by farmers in their work, farm commodity which has post- harvest failure (4) farm commodity product tent to based on the past experience and didn t base on inovation (5) government role in develop farm was limited and wasn t routine. Efforts to create development in agropoly region in Batu City region was fit with the potential, needed a major plan mechanism consisted of : decision taking by people mechanism, partnership mechanism, cooperation between entrepreneur, government, and private, investment mechanism, and information system development in form Agropoly Region Information Center. The mechanism was described in activity or implementation : program arrangement and education activity and development also the supporting program.